Exclusion of Smallholders in the Indonesia Palm Oil Industry - Rahayu, Neneng Sri; Nugroho, Alih Aji; Yusuf, Rima Ranintya (KnE Social Sciences, 2022)
Indonesia produces and exports the most palm oil in the world. In practice, palm oil farmers are regarded as one of the most important contributors to the global palm oil industry chain’s trajectory. Farmers were actively involved in the Core-Plasma Plantation mechanism with the Member Primary Credit Cooperative (KKPA) scheme. However, putting this ideal picture into practice proved difficult, resulting in a slew of issues. Conflicts frequently arose as a result of the KKPA in Riau Province, home to Indonesia’s largest palm oil plantation. Community advocacy teams in three villages in Tambang District, Kampar Regency, informed the Regent about the polemics that occurred in the KPPA nucleus-plasma scheme involving village unit cooperatives, the community, and parent companies. The goal of this article was to investigate how the KKPA was implemented, and how it resulted in smallholders being excluded. This qualitative study relied on interviews with cooperative management, farmer groups, PTPN (a state-owned enterprise in the plantation sector) as the core company, plantation officers and farmers in Riau Province. The study was conducted from May to June 2021, and it revealed that the KKPA’s implementation was far from ideal. Farmers were excluded from the development of the palm oil industry. Parties’ rights and obligations were subject to asymmetrical information or bias. Farmers have lost control of their own land as a result of the size of the deduction from their harvest. The data on the debts and total instalments that have been paid must be made public so that the public is aware of the shortfall and timeframe. Keywords: exclusion of palm oil smallholders, nucleus-people plantations, KKPA